Verbs of Anger and Intimately Related Emotions: : A Lexical Constructional Account - van Arkel-Simón, Carlos (International Journal of English Studies, 2025)
This paper analyses the domain of verbs of anger and closely related emotions in order to implement a formalised lexical constructional account. Through a detailed analysis of psych-verbs, this research explores their syntactic and semantic specifications. By investigating the roles of experiencers and stimuli arguments either as syntactic subject or object when causing changes in psychological states, the study attempts to shed light on the syntactic and semantic properties of anger and related verbs and the constructions in which they occur. Drawing on constructional and lexical templates for argument structure, this study provides a detailed mapping of how language lexicalises verbal predicates of anger. Overall, this research offers an insight into their formalised representation, relying on the general principles of the Lexical Constructional Model (LCM) (Ruiz de Mendoza & Galera-Masegosa, 2014; Ruiz de Mendoza & Mairal-Usón, 2007, 2008, 2011), Role and Reference Grammar (RRG) (Bentley et al., 2023; Van Valin, 2005; Van Valin & La Polla, 1997), and Construction Grammar (CxG) (Fillmore & Kay, 1996; Goldberg, 1995, 2006; Hoffmann, 2022; Michaelis, 2013; Sag & Boas, 2012).